Virtual Witness Testimony in Criminal Cases During the COVID-19 Pandemic: A Study on Evidence in the Banda Aceh Sharia Court - Salim, Mohammad; Umar, Mukhsin Nyak; Saputra, Rahmat; Dault, Wisnu Adiyaksa; Ath-Thayyar, Muhammad Hafidh (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study discusses the legal certainty of electronic criminal trials, particularly the presentation of witness testimony virtually during the COVID-19 pandemic. Guidelines for electronic criminal trials are needed to ensure uniform implementation and to uphold fair trial rights. As a province with the authority of the Syar'iyah Court, Aceh should be able to anticipate the spread of COVID-19 by implementing electronic trials. The research focuses on the regulations related to electronic trials, specifically the presentation of witness testimonies virtually as evidence in criminal cases, and the practices implemented at the Banda Aceh Sharia Court. This research uses a descriptive-analytical method with a qualitative approach. The sources of data for the research are field research and library research. The research results show that the form of legal certainty regarding electronic criminal trials or jinayat during the COVID-19 pandemic is the agreement on cooperation between the Supreme Court, the Prosecutor's Office, and the Ministry of Law and Human Rights on the Implementation of Trials Through Teleconference, which was then established by Supreme Court Regulation Number 4 of 2020 concerning the Administration and Trial of Criminal Cases in Court Electronically. In practice, the Banda Aceh Sharia Court determined that the presentation of witness testimony during the COVID-19 pandemic must be conducted in the courtroom. However, it is still carried out virtually to connect with the defendant in the detention center or prison where he is held.